Endothelial Dysfunction in Systemic Lupus Erythematosus and Systemic Sclerosis: A Common Trigger for Different Microvascular Diseases - Moschetti, Liala; Piantoni, Silvia; Vizzardi, Enrico; Sciatti, Edoardo; Riccardi, Mauro; Franceschini, Franco; Cavazzana, Ilaria (Frontiers in Medicine, 2022)
This review describes the complex interplay between inflammation, vasculopathy and fibrosis that involve the heart and peripheral small vessels, leading to endothelial stiffness, vascular damage, and early aging in patients with systemic lupus erythematosus and systemic sclerosis, which represents two different models of vascular dysfunction among systemic autoimmune diseases. In fact, despite the fact that diagnostic methods and therapies have been significantly improved in the last years, affected patients show an excess of cardiovascular mortality if compared with the general population. In addition, we provide a complete overview on the new techniques which are used for the evaluation of endothelial dysfunction in a preclinical phase, which could represent a new approach in the assessment of cardiovascular risk in these patients.